EP.TH.243Western Australian Multicentre review of management of the axilla in breast cancer patients receiving neoadjuvant chemotherapy. (28th October 2021) - MacConnell, Suanne; Ballal, Helen; Singh, Vineeta; Saunders, Christobel
Abstract: Aim: De-escalation of treatment in early breast cancer is proposed to reduce morbidity to patients without compromising oncological outcomes. Use of SNB as gold standard in clinically node negative patients is an example of successful implementation. In patients receiving upfront chemotherapy, axillary management is more complex. We reviewed the axillary management of patients undergoing neoadjuvant chemotherapy (NAC) to assess nodal response. Method: The MDT records of two centres were reviewed between January 2015 and May 2019 to identify patients receiving NAC. Clinical records were reviewed to collect demographics, radiological and clinicopathological results as well as follow up data. Results: 185 patients were identified as suitable, median age 49 (21-79). 49% were clinically node negative on presentation. 32% underwent a SNB prior to NAC; this decreased over the study period from 40.5% to 20.5%. Of the cN0 patients, 24% were upstaged to node positive disease at final surgery. None of these achieved a pCR in the breast. 18% of cN0 patients went straight to ALND, 50% were YpN0. 42% of cN1 patients achieved ypN0. 58% down-staged to ypN0 also achieved pCR in the breast. Only 1 patient with residual disease in axilla achieved pCR in the breast. Conclusion: Use of pre-NAC SNB is declining with low rates of upfront ALND in cN0 patients. There is a 42% rate of down-staging axillary disease with NAC. Patients are unlikely to have nodal response without pCR in the breast. There is likely to be a role for targeted axillary dissection in carefully selected patients.